PENGARUH E-RECOVERY SERVICE QUALITY TERHADAP REPURCHASE INTENTION DENGAN E-CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING - Dewi, Putri Puspita; Sudarwanto, Tri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022, 2022)
This research aims to determine how much e-recovery service quality influences repurchase intention through e-customer satisfaction as an intervening variable for Shopee users at the State University of Surabaya. This study used a population of 150 active students and a sample of 108 respondents. Data collection using a questionnaire and data analysis using Partial Least Square (PLS) with the help of the SmartPLS application version 3.3.9. The results of the study prove that the direct relationship of e-recovery service quality is able to affect e-customer satisfaction with a value of 13,218 and the direct relationship of e-customer satisfaction is able to influence repurchase intention with a value of 8090, while the direct relationship of e-recovery service quality is not able to affect repurchase intention because it is only worth 0.285. However, in the indirect relationship, e-customer satisfaction has succeeded in being the perfect mediation for e-recovery service quality on repurchase intention with a value of 6,701. The results of this study can be used as a reference for students in learning activities and further research development.